The Influence Of Body Mass Index And Eating Patterns On Cholesterol Levels In Adolescents - Sahrul Gunawan; Firdawsyi Nuzula; Maulida Nurfazriah oktaviana (PROFESSIONAL HEALTH JOURNAL, 2025)
Introduction: Unhealthy eating habits, such as the consumption of junk food that is high in salt, sugar, and low in nutrients, can lead to nutritional deficiencies and increase the risk of early cardiovascular diseases in adolescents. Objectives: This research aims to analyze the relationship between dietary patterns and Body Mass Index (BMI) with cholesterol levels in adolescents. Methods: This study uses a cross-sectional analytical observational design. In this study, the sample used total sampling. The population of 58 respondents means that the sample taken is 58 samples. The data was analyzed using univariate analysis for the frequency distribution of BMI, dietary patterns, and cholesterol levels. The chi-square test is used in bivariate analysis to assess the relationship between diet and BMI with cholesterol levels. Results: Based on 58 respondents, the analysis using the chi-square test found that the significance level of the p-value is 0.05, as (p-value 0.464) indicates that there is no effect of BMI on cholesterol levels. Conclusions: Meanwhile, the analysis using the chi-square test on diet concerning cholesterol levels yielded a (p-value of 0.001), indicating that diet affects cholesterol levels. The research results indicate that BMI does not have a significant effect on cholesterol levels, while dietary patterns do impact cholesterol levels among adolescents. This indicates that a multifactorial approach is necessary for addressing cholesterol issues in adolescents.